Building a technopolis - a critical analysis of Malaysia's multimedia super corridor. - Chua, Yang Boon. (2008)
As part of Malaysia's Vision 2020, Malaysia embarked on a bold project - the Multimedia Super Corridor (MSC) - adopt the Information Age approach to economic development. Malaysia aims to develop MSC into a technopolis: an area with an agglomeration of high-technology firms. This report presents an overview of the underlying forces that bring about this clustering phenomenon and the benefits that arise through the concentration of firms.